Attitude of Rice Farmers toward the Intermittent Water Management in the Snake River Irrigation Area of North Sumatra Province of Indonesia - . Wasito; Bachtar Bakrie; Sortha Simatupang; . Khairiah; . Sukardi (Current Advances in Geography, Environment and Earth Sciences Vol. 4, 2022)
The irrigated rice fields in the study area were Serdang Bedagai and Deli Serdang Regencies in the Snake River watershed area. Intermittent water management is a technological component of the integrated rice crop management (IRCM) program. A study has been conducted to determine the extent to which the attitude of farmers to the technology components. This study has been carried out continuously in Lubuk Bayas Village (Serdang Bedagai Regency) since 2003, as the initial area where introduced the ICRM program in 2002. In addition, we conducted the research continuously in several villages in Perbaungan, Pantai Cermin and Serbajadi Subdistricts (Serdang Bedagai Regency). Also in Pagar Merbau, Beringin, and Tanjung Morawa/Lubuk Pakam sub-districts (Deli Serdang Regency). Primary data collection begins with observing and engaging in communities (natural settings). The next stage was to determine the sample purposively to pioneer farmers (innovators or early adopters). In addition, we also carried out secondary data studies and a review of research results. It discovered that farmers do not apply the intermittent irrigation technology since the early introduction of the ICRM program in 2002, even though they have a moderate level of knowledge. In general, the attitude of farmers was never to try first because, technically, socio-economically, they were experiencing difficulties. The existence of irrigation water and land ownership was not supportive, and the relatively flat topography of the area, although irrigation institutions were adequate. In addition, they have an ambiguous attitude towards other environmentally friendly technologies, namely the technology of using fertilizers from rice straw waste and manure (ecological approach). This attitude was influenced by the experience and culture of the farming community, including habits that are difficult to change.